Aaron Copland and the American legacy of Gustav Mahler - Mugmon, Matthew (Eastman studies in music, 2019)
"Although Aaron Copland (1900-1990) is often credited with creating an unmistakably American musical style, he was strongly attracted to the music of Gustav Mahler. Drawing extensively on archival and musical materials, this is the first detailed exploration of Copland's multifaceted relationship with Mahler's music and its lasting consequences for music in America. Matthew Mugmon demonstrates that Copland, inspired by Mahler's example, blended modernism and romanticism in shaping a vision for American music in the twentieth century, and that he did so through his multiple roles as composer, teacher, critic, and orchestral tastemaker. Copland's career-long engagement with Mahler's music intersected with Copland's own Jewish identity and with his links to such towering figures in American music as Nadia Boulanger, Serge Koussevitzky, and Leonard Bernstein"--